A performance of becoming: Embroidering self into otherness - Scott, Joy Denise (Routledge, 2011)
In this paper I write about my embodied experiences of existence inside, outside and between two very different cultures, Australia and China. My intention in this paper is to unravel some of the many layers of lived experience of a western teacher creating meaning in the face of constant cultural misunderstandings. In revisiting the memories and experiences of my life in Shanghai I negotiate and interrogate my internal border-crossings and in-betweener states in order to translate previous impressions and sensory experiences into new embodied awareness. I value the border-crossings and in-between states and the deeper reflexive thinking they generate, because they allow me to see behind the heavily embroidered veil of ideological delusion.